The role of apologies in the resolution of medical disputes - Jahn Kassim, Puteri Nemie; Saleh, Muhammad Ridhwan (2016)
In the wake of medical errors and potential lawsuits, apologies made by the medical practitioner to the patient have the ability to defuse the spur of litigation and restore the relationship of trust and confidence between them. Often, when things go wrong in a medical treatment, the patient wants to know what actually happened, why it happened and be assured that it will not happen again in the future. At this juncture, apologies which are ‘statements acknowledging error and its consequences, including accepting responsibilities and communication of regrets’ can reduce the intensifying anger and desires to retaliate. Nevertheless, apologies may also have the potential to be seen as admissions of guilt by the medical practitioner and may at certain circumstances, expose him to risks of impending lawsuits. In weighing the drawbacks of apologies against their benefits, several countries have enacted ‘apology laws’ that mandate open disclosure of medical errors and at the same time, shielding those who apologise from legal liability. For instance, Canada and Australia have enacted ‘apology laws’ in which apologies that have been given after adverse events cannot be used in future legal proceedings. This paper seeks to discuss the role of apologies in the resolution of medical disputes, particularly, in reducing the number of potential lawsuits and promoting prospects of settlement. Against this backdrop, the barriers faced by the medical practitioners in subjecting themselves to acts of open disclosure after a mishap should not be overlooked to ensure the inculcation of a sustainable culture of honesty, openness and respect that is fundamental for patient safety improvements and public trust within the healthcare system.